Plasmalogens Regulate Retinal Connexin 43 Expression and Müller Glial Cells Gap Junction Intercellular Communication and Migration - Karadayi, Rémi; Mazzocco, Julie; Leclere, Laurent; Buteau, Bénédicte; Gregoire, Stéphane; Belloir, Christine; Koudsi, Mounzer; Bessard, Pauline; Bizeau, Jean-Baptiste; Dubus, Elisabeth; Fenech, Claire; Briand, Loïc; et al. (Frontiers in Cell and Developmental Biology, 2022)
Plasmalogens are a specific glycerophospholipid subtype characterized by a vinyl-ether bound at their sn-1 moiety. Their biosynthesis is initiated in the peroxisome by dihydroxyacetone phosphate-acyltransferase (DHAPAT), which is encoded by the DAPAT gene. Previous studies have shown that plasmalogen-deficient mice exhibit major physiological dysfunctions including several eye defects, among which abnormal vascular development of the retina and a reactive activation of macroglial Müller cells. Interestingly, plasmalogen deficiency in mice is also associated with a reduced expression of brain connexin 43 (Cx43). Cx43 is the main connexin subtype of retinal glial cells and is involved in several cellular mechanisms such as calcium-based gap junction intercellular communication (GJIC) or cell migration. Thus, the aim of our work was i) to confirm the alteration of Cx43 expression in the retina of plasmalogen-deficient DAPAT-/- mice and ii) to investigate whether plasmalogens are involved in crucial functions of Müller cells such as GJIC and cell migration. First, we found that plasmalogen deficiency was associated with a significant reduction of Cx43 expression in the retina of DAPAT-/- mice in vivo. Secondly, using a siRNA targeting DHAPAT in vitro, we found that a 50%-reduction of Müller cells content in plasmalogens was sufficient to significantly downregulate Cx43 expression, while increasing its phosphorylation. Furthermore, plasmalogen-depleted Müller cells exhibited several alterations in ATP-induced GJIC, such as calcium waves of higher amplitude that propagated slower to neighboring cells, including astrocytes. Finally, in vitro plasmalogen depletion was also associated with a significant downregulation of Müller cells migration. Taken together, these data confirm that plasmalogens are critical for the regulation of Cx43 expression and for characteristics of retinal Müller glial cells such as GJIC and cell migration.